MathOverflow is a question and answer site for professional mathematicians. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prove/ Disprove: Let $n$ be a positive integer. Let $A$, $B$ be two $n \times n$ square matrices over the complex numbers. If $AB = BA$ and $\ker A = \ker A^2$ and $\ker B = \ker B^2$ then $\ker AB = \ker A + \ker B$.

(Recall that $\ker A$ is the set of all vectors $v$ such that $Av = 0$.)

Background: I am teaching linear algebra this semester. I did not like the standard proof of the Jordan canonical form I found in the textbooks, and thought I could prove it differently, directly from the axioms for a vector space, without using either the determinant, or the classification theorem for finite abelian groups. If the statement above is true, I believe I have a proof for the Jordan canonical form for $T$ by setting $A = (T-\lambda_1I)^{n_1}$ and $B=(T-\lambda_2I)^{n_2}$ for appropriate $n_1$ and $n_2$.

Note 1: If $A = B = \left( \begin{array}{cc} 0 & 1\\\0 & 0 \end{array} \right)$ then $AB = BA$ but $\ker AB \neq \ker A + \ker B$.

Note 2: It is easy to find $A, B$ such that $\ker A = \ker A^2$ and $\ker B = \ker B^2$ and $B$ maps a vector outside $\ker A + \ker B$ to $\ker A$, so that $\ker AB \neq \ker A + \ker B$.

Hence, both conditions are necessary.

share|cite|improve this question
A neat proof of the Jordan canonical form can be found here: (in german). In particular, Satz 1 might interest you. – Martin Brandenburg Nov 5 '11 at 10:07
Thanks, Martin. Satz 1 would certainly give me the kind of proof I am looking for. If I'm not mistaken, it says that: Claim: If g,h are polynomials in one variable whose gcd is 1, then for every endomorphism $\alpha$, the kernel $\ker (gh)(\alpha)$ is a direct sum of $\ker g(\alpha)$ and $\ker h(\alpha)$. Proof: 1. If there is a vector $v$ in the intersection of the kernels of $g(\alpha)$ and $h(\alpha)$, then its annihilator (in the polynomial ring) is trivial, so $v=0$. 2. Proves the easy direction of the inclusion: $\ker g(\alpha) \subseteq \ker (gh) (\alpha)$. 3. $\alpha$ commutes wi – Manoj Nov 5 '11 at 11:50
3. $\alpha$ commutes with $W=\ker (gh)(\alpha)$, so $W$ is invariant under $\alpha$. Let $\gamma$ be the restriction of $\alpha$ to $W$. We have already shown that the two other kernels of interest live inside $W$. 4. Restricted to $W$, we know that $(gh)(\gamma)$ is identically zero. Therefore the image of $h(\gamma)$ must be contained in the kernel of $g(\gamma)$. [The proof seems to get this backwards. Perhaps they are using left multiplication?] 5. But NOW! $dim(\ker h(\gamma)) + dim(im h(\gamma)) = dim W$ by the rank-nullity theorem! 6. Therefore, $dim(\ker h(\gamma)) + dim(\ker g(\ga – Manoj Nov 5 '11 at 11:51
6. Therefore, $dim(\ker h(\gamma)) + dim(\ker g(\gamma)) >= dim W$. But hold on, these kernels intersect trivially, as we already showed. So we're done! – Manoj Nov 5 '11 at 11:51
I believe you might be interested in the book Linear Algebra Done Right by Sheldon Axler. He has a similar dislike of determinants. – Loop Space Nov 5 '11 at 22:34
up vote 27 down vote accepted

Since $\ker A = \ker A^2$, the map $\bar{A} : V/\ker A \to V/\ker A$ is injective. Since $V/\ker A$ is finite dimensional, this map is surjective. So for any $x \in V$ we can find $y \in V$ and $z \in \ker A$ such that $x = Ay + z$.

Now suppose $ABx = 0$ and let $x = Ay + z$ as above. Then $0 = ABx = ABAy + ABz = A^2By + BAz = A^2By$ because $AB = BA$ and $Az = 0$.

So $By \in \ker A^2 = \ker A$ whence $ABy = 0$. So $B(Ay) = 0$ and $Ay \in \ker B$.

Hence $x = Ay + z \in \ker B + \ker A$.

share|cite|improve this answer
1+. More generally, for an artinian object $V$ in an abelian category and two commuting endomorphisms $A,B$ of $V$ such that $\ker(A^2)=\ker(A)$ and $\ker(B^2)=\ker(B)$ (as subobjects of $V$), then $\ker(AB)=\ker(A) + \ker(B)$ (as subobjects of $V$). – Martin Brandenburg Nov 5 '11 at 15:10
+1. Very neat proof. – Todd Trimble Nov 5 '11 at 15:50
+1. Why don't all books approach the JCF theorem the way suggested in this post? – Bill Johnson Nov 5 '11 at 18:00
Thanks, Konstantin. It is a very neat proof! I notice that you did not make use of the assumption that $\ker B^2 =\ker B$. – Manoj Nov 6 '11 at 3:11
So you seem to have proved something stronger: If $AB=BA$ and either $\ker A = \ker A^2$ or $\ker B=\ker B^2$ then $\ker AB=\ker A+\ker B$. – Manoj Nov 6 '11 at 3:13

Here is a proof. First notice that the space of all matrices of size $n$ is finite dimensional. Therefore matrices $A,...,A^{m}$ are linearly dependent for a sufficiently large $m$ (this is instead of Hamilton-Cayley). Hence there exists a polynomial $f(x)$ such that $f(A)=0$, $f(0)=0$. Represent $f(x)$ as $x^kg(x)$ where $g(0)\ne 0$, $k\ge 1$. Dividing by $g(0)$ we can assume that $g(0)=1$. We have $A^kg(A)=0$. Hence $Ag(A)=0$ (since $Ker A= Ker A^2$). Now let $ABx=0$. We have that $(g(A)-1)x=A*h(A)x$ (for some $h$), so $(g(A)-1)x$ is in $Ker B$. Since $g(A)x$ is in the kernel of $A$, we have the decomposition $x=g(A)x-(g(A)-1)x$ where the first summand in $Ker A$, the second in $Ker B$.

share|cite|improve this answer
Thanks, Mark, quite a nice proof. – Manoj Nov 6 '11 at 3:21

Here's another statement of more or less the same result. The ideas in the proof are from this proof in German that Martin Brandenburg linked to in his comment.

Claim: Let $n$ be a non-negative integer. Let $A$, $B$ be two $n×n$ square matrices over the complex numbers. If $AB=BA$ and $\ker A \cap \ker B = \{0\}$ then $\ker AB=\ker A \bigoplus \ker B$.

Note: Assuming that $\ker A\cap\ker B=\{0\}$ is not a big restriction, since we can always quotient out to eventually reduce to this case.

Proof: Since $A,B$ commute, it is clear that $\ker A \bigoplus \ker B\subseteq \ker AB$. Further, $\ker AB$ is invariant under $A, B$. Since all the action is taking place within $\ker AB$, we may assume without loss of generality that $\ker AB$ is the entire space, of dimension $n$. This implies $\operatorname{im} B\subseteq \ker A$.

By the rank-nullity theorem, $\dim\ker B + \dim\operatorname{im} B = n$. Hence, $\dim\ker A + \dim\ker B\geq n$. Since these spaces intersect trivially by assumption, we are done.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.